2011
DOI: 10.1017/s1751731110002600
|View full text |Cite
|
Sign up to set email alerts
|

Use of partial least squares regression to predict single nucleotide polymorphism marker genotypes when some animals are genotyped with a low-density panel

Abstract: High-density single nucleotide polymorphism (SNP) platforms are currently used in genomic selection (GS) programs to enhance the selection response. However, the genotyping of a large number of animals with high-throughput platforms is rather expensive and may represent a constraint for a large-scale implementation of GS. The use of low-density marker (LDM) platforms could overcome this problem, but different SNP chips may be required for each trait and/or breed. In this study, a strategy of imputation indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
(17 reference statements)
0
14
0
Order By: Relevance
“…PLSR is a multivariate statistical covariance-based technique that is able to predict a response matrix Y ( n × p ) from a predictor matrix X ( n × m ) and to describe the common structure of the two matrices [18]. In both X and Y , n represents the number of animals involved, m is the number of SNPs in the LDP and p is the number of SNPs to be imputed.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…PLSR is a multivariate statistical covariance-based technique that is able to predict a response matrix Y ( n × p ) from a predictor matrix X ( n × m ) and to describe the common structure of the two matrices [18]. In both X and Y , n represents the number of animals involved, m is the number of SNPs in the LDP and p is the number of SNPs to be imputed.…”
Section: Methodsmentioning
confidence: 99%
“…PLSR allows for the identification of underlying variables (known as latent factors) which are linear combinations of the explanatory variables X , that best model Y . Dimauro et al [18] demonstrated that the accuracy of PLSR prediction increases with the number of latent factors approaching the number of SNPs to be predicted (the columns of Y ). The maximum number of latent factors depends on the size of X , which has a lower number of columns than Y .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations